Cognition in liver disease - Collie, Alexander (Liver international, 2005)
: Background: Cognitive dysfunction has been observed in a range of liver diseases including chronic hepatitis C virus, alcoholic liver disease, primary biliary cirrhosis and Wilson's disease. Such dysfunction may range from mild cognitive changes to overt hepatic encephalopathy, and represents a significant complication of liver disease that may negatively impact the patient's quality of life, and normal activities of daily living (e.g., driving). Method: This article reviews the published evidence relating to cognitive dysfunction in liver disease. Outcome: Issues of definition, diagnosis, epidemiology, aetiology, treatment and outcome are discussed. Particular attention is devoted to identifying the mild cognitive changes that occur in liver diseases of different aetiology.